Sistemática filogenética dos Gecarcinidae H. Milne Edwards (Crustacea - Brachyura) - Tavares, Marcos Domingos Siqueira (1989)
This paper deals with the phylogenetic systematics of land crabs of the family Gecarcinidae. It includes the recognition and description of the gecarcinid genera as well species of Gecarcinus. Emphasis is placed on the reconstruction of their phylogeny. Sixty-six morphological characters were selected and analysed for the phylogenetic reconstructions. The out- group comparison method was used for distinguishing plesiomorphic and apomorphic character states. The family Grapsidae was selected as out-group. The worldwide family Gecarcinidae includes the following genera: Ca rdisoma, Epigrapsus, Gecarcoidea and Gecarcinus. The genus Ucides has in the past been included in the Gecarcinidae, but has now been transferred to the family Ocrpodidae. Gecarcinidae and Grapsidae p rove to be sister-groups. The subgenera Gecarcinus and John garthia are rejected and Gecarcinus quadratus resurrected from the sinony mi of Gecarcinus lateralis. Extincti ons events in the history of thegecarcini ds are discussed.